Case report: A case report of co-morbidity of cervical intraepithelial neoplasia III and urethral cancer associated with HPV16 - Zhu, San; Liu, Yuhao; Bian, Ce; Luo, Yan; Zhu, Manman; Yang, Lingyun (Frontiers in Oncology, 2024)
In this report, we present a case of a woman with concurrent cervical intraepithelial neoplasia grade III (CIN III) and urethral cancer, both associated with HPV16 infection. This unique case was initially brought to attention due to postmenopausal vaginal bleeding, despite the absence of urological symptoms and negative tumor markers. An unexpected discovery of pelvic lymph node metastasis during a hysterectomy intended for CIN III highlighted the rare coexistence of these conditions, with urethral cancer also linked to HPV-16 within the urethral lesion. This case emphasizes the diagnostic challenges faced by HPV-related cervical lesions and the critical need for increased vigilance, even when urological symptoms are not apparent. The findings underline the potential complexity of HPV-associated lesions and advocate for comprehensive screening strategies to ensure the timely detection and management of such intricate cases.